IMPROVING THERMAL PERFORMANCE OF MICRO CHANNEL ELECTRONIC HEAT SINK USING SUPERCRITICAL C02 AS COOLANT - SARKAR J. (My University, 2025)
In view of increasing tendency of power density of electronic systems, cool-ing performance improvement of micro-channel heat sink is an emerging issue. In the present article, supercritical CO2 is proposed as a heat transfer fluid in micro-channel heat sink for power electronics cooling. Energetic and exergetic performance analyses of micro-channel heat sink using supercritical CO2 have been done and compared with conventional coolant, water. To take care of sharp change in properties in near critical region, the discretization technique has been used for simulation. Effects of both operating and geometric parameters (heat flux, flow rate, fluid inlet temperature, channel width ratio, and channel numbers) on thermal resistance, heat source (chip) temperature, pressure drop, pumping power and entropy generation are presented. Study shows that the thermal resistance, heat source temperature and pumping power are highly dependent on CO2 inlet pressure and temperature. Supercritical CO2 yields better performance than wa-ter for certain range of fluid inlet temperature. For the studied ranges, maximum reduction of thermal resistance by using CO2 is evaluated as 30%. Present study reveals that there is an opportunity to use supercritical CO2 as coolant for power electronic cooling at lower ambient temperature. © (publication year), (publisher). All rights reserved.